1996
DOI: 10.1128/jb.178.8.2343-2350.1996
|View full text |Cite
|
Sign up to set email alerts
|

A complex four-gene operon containing essential cell division gene pbpB in Bacillus subtilis

Abstract: We have cloned and sequenced the promoter-proximal region of the Bacillus subtilis operon containing the pbpB gene, encoding essential penicillin-binding protein PBP2B. The first two genes in the operon, designated yllB and yllC, are significantly similar to genes of unknown function similarly positioned upstream of pbpB in Escherichia coli. Both B. subtilis genes are shown to be nonessential. The third B. subtilis gene, yllD, is essential, as is the correspondingly positioned ftsL gene of E. coli. The predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 22 publications
(20 reference statements)
7
80
0
1
Order By: Relevance
“…Therefore, it can be concluded that ftsI is mainly cotranscribed along with the mraZ, mraW, ftsL and murE genes of the operon probably from the Pmra promoter, as described in E. coli and B. subtilis (Hara et al, 1997), and probably also from a minor promoter (PftsI) as in B. subtilis (Daniel et al, 1996). This result also suggests that the second GTG (at position 2 293 165) most probably is the start codon of ftsI.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Therefore, it can be concluded that ftsI is mainly cotranscribed along with the mraZ, mraW, ftsL and murE genes of the operon probably from the Pmra promoter, as described in E. coli and B. subtilis (Hara et al, 1997), and probably also from a minor promoter (PftsI) as in B. subtilis (Daniel et al, 1996). This result also suggests that the second GTG (at position 2 293 165) most probably is the start codon of ftsI.…”
Section: Resultssupporting
confidence: 56%
“…Furthermore, the localization of GFP-FtsI at the mid-cell is strongly indicative of the involvement of FtsI in C. glutamicum cell division, most likely in the biosynthesis of septum peptidoglycan as described for other bacteria. ftsI seems to be an essential gene in C. glutamicum ftsI has been shown to be an essential gene in E. coli (Begg et al, 1992) and in B. subtilis (Daniel et al, 1996). Therefore, in order to determine whether ftsI was also necessary for the viability of C. glutamicum, we performed gene disruption experiments using the suicide plasmid pKInt1 (Table 1); all attempts to inactivate the ftsI gene using internal fragments were unsuccessful, similar to our earlier studies involving murC, another essential gene in C. glutamicum (Ramos et al, 2004).…”
Section: Visualization Of Ftsi Cg -Gfp Fusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and Table 2). Both ftsL and pbpB are essential for cell division (34). FtsL is an unstable protein (35,36); a decrease in ftsL mRNA levels quickly causes a decrease in FtsL protein and inhibits cell division (37).…”
Section: Repression Of An Essential Cell Division Gene Couples Replicmentioning
confidence: 99%
“…Likewise, strains of Bacillus subtilis lacking PBP1, PPB2c, PBP2d, and PBP4 (either alone or in various combinations) display little to no change in peptidoglycan cross-linking ratios (16). Genetic deletion of PBP2b in B. subtilis is lethal, suggesting that it may play a primary role in TP activity (17). Together, these examples highlight the limitations of using genetic manipulations alone to track PBP enzymatic activity.…”
mentioning
confidence: 99%